Stakeholders facing renewable energy projects in Yucatán: Ticul Solar Farm - García-Beltrán, Yolanda (2024)
Introduction: This work is based on research that documents the reasons that lead to the rejection, or not, of wind and photovoltaic energy projects in Yucatán, Mexico. Based on this, this text begins with an analysis of the stakeholders strategies Objective: The objective of this text is to document and analyze the opinions and positions of the different stakeholders involved, specifically, in the case of the Ticul Solar Farm, with an emphasis on local residents. it seeks to answer the following question: How do community stakeholders intervene around the installation of renewable energy projects in Yucatan and, specifically in the case of the Ticul Solar Farm, how do they interact and what actions and strategies do they carry out to achieve their objectives? Methodology: Qualitative research methods are used The basis of the information lies in semi-structured interviews, also review and analysis of different documentary sources Conclusions: The results show that alliances between stakeholders are an essential part of the strategies forged, but that these are changing. In addition, there are multiple power relations that materialize in the territory, which are asymmetrical.